Managerial challenges of outbound open innovation: a study of a spinout initiative in AstraZeneca. (12th December 2018) - Remneland Wikhamn, Björn; Styhre, Alexander
Abstract : While the research on open innovation is flourishing, less attention has so far been given to 'outbound' processes in comparison to 'inbound' and 'coupled' open innovation. In this paper we analyze a qualitative case study of the global bio‐pharmaceutical company AstraZeneca and their attempt to establish a spinout initiative where internal projects are transferred to entrepreneurial startups funded by external venture capital. We explain the enactment work of this initiative and identify three emerged managerial challenges, linked to (1) internal decision‐making, (2) the cultural and psychological barriers of what we phrase as the 'not‐invented‐elsewhere' (NIE) syndrome, and (3) the ability to translate and communicate internal projects as attractive external proposals. Theoretical and managerial implications in relation to these challenges are outlined and discussed.